Ethnoscience-Based Inquiry Learning to Increase Students’ Critical Thinking Skills and Collaboration Skills - Cut Nurul Fitri; Saminan; Rini Safitri; Teuku Muhammad Hary Ramadhan; Evendi; Safrida S (Jurnal Penelitian Pendidikan IPA, 2024)
The goal of this study is to increase students' CTS and CS about quantity and unit material using ethnoscience-based inquiry learning. The study utilized a non-equivalent control group design with two classes: experimental and control. The sample in this study were students of class X IPA 7 and X IPA 8, who were chosen using purposive sampling procedures. The research sample comprised 71 students. The research data was gathered using 15 multiple-choice questions, a CTS questionnaire, and a CS questionnaire. Normality, homogeneity, the t-test, and correlation tests were employed to analyze the data. Based on the research findings, students' CTS and CS rose in the experimental class, with N-gain values of 0.71 (high) and 0.60 (medium). The experimental and control courses showed significant differences in students' CTS and CS outcomes (Sig. < 0.05). Aside from that, there is a very strong correlation between students' CTS and CS results in learning, with r = 0.938. It may be concluded that using an ethnoscience-based inquiry paradigm can help students enhance their CTS and CS. Thus, it is possible to infer that ethnoscience-based inquiry learning may increase students' CTS and students' CS. There is a very strong correlation between CTS and students' CS.